Genetic analysis of Staphylococcus aureus with Tn4001. - Mahairas, G G (1989)
Tn4001, a 4.5-kilobase composite transposon with IS256 ends that confers resistance to gentamicin (Gmr), tobramycin, and kanamycin in Staphylococcus aureus, can transpose to diverse chromosomal sites in S. aureus. Chromosomal insertions of Tn4001 were isolated either after UV irradiation of transducing lysates carrying pII147::Tn4001 or by selection for thermoresistant Gmr isolates with strains containing thermosensitive derivatives of plasmids pI258 and pII147 carrying Tn4001. Frequent integration of the entire delivery plasmid occurred under these selective conditions in recombination-proficient hosts. When selection for thermoresistant Gmr isolates was done with these plasmids in recombination-deficient hosts, 99% or more of the Gmr isolates resulted from transposition of Tn4001 in the absence of plasmid integration. Efficient isolation of Tn4001 insertions near markers of interest and the isolation of insertional auxotrophs were achieved. Reversion frequencies of insertional auxotrophs were between 10(-6) and 10(-7) (higher than those observed with Tn551 and Tn917). About 50% of the prototrophic revertants were Gms, and these are attributed to precise excision of Tn4001. The Gmr prototrophic revertants were due to intergenic suppression.